2023
DOI: 10.1007/s00421-023-05160-0
|View full text |Cite
|
Sign up to set email alerts
|

Decrements of mobility and power in recreationally active septuagenarians is related to loss of force, but not slowing of the muscle: a 5-year longitudinal study

Abstract: A lesser 6-min walk distance (6MWD) and timed up-and-go (TUG) in old compared with young adults was previously linked to slowing of muscle contractile properties. The purpose of the present study was to determine whether any further reductions in 6MWD and TUG over a 5-year period in septuagenarians are associated with further slowing of muscle contractile properties. We measured muscle function by a countermovement jump, isometric maximal knee extensor strength (MVC) on a dynamometer and quadriceps muscle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…Indeed, after the age of 70, the muscle mass declines by 0.5-1.0% per year, the decline being different by sex, close to 1% per year in men and 0.7% per year in women after 75 years, with an even steeper decline in muscle strength of 3-4% in men and 2.5-3% women. Recently, Cameron et al [10] showed that over 5year period healthy septuagenarians lost about 4.5-5% of their appendicular lean muscle mass and Teraz et al [11] reported a 4.5% decrease of skeletal muscle index over an 8 period of follow up of 69 healthy and active older adults (mean baseline age 68.3 years). It is worthy of note that, however, the age-related changes are not uniform across all muscles and the extent of sarcopenia varies between muscles in different locations with different functions.…”
Section: Epidemiologymentioning
confidence: 99%
“…Indeed, after the age of 70, the muscle mass declines by 0.5-1.0% per year, the decline being different by sex, close to 1% per year in men and 0.7% per year in women after 75 years, with an even steeper decline in muscle strength of 3-4% in men and 2.5-3% women. Recently, Cameron et al [10] showed that over 5year period healthy septuagenarians lost about 4.5-5% of their appendicular lean muscle mass and Teraz et al [11] reported a 4.5% decrease of skeletal muscle index over an 8 period of follow up of 69 healthy and active older adults (mean baseline age 68.3 years). It is worthy of note that, however, the age-related changes are not uniform across all muscles and the extent of sarcopenia varies between muscles in different locations with different functions.…”
Section: Epidemiologymentioning
confidence: 99%